2021
DOI: 10.1038/s41598-021-02544-0
|View full text |Cite
|
Sign up to set email alerts
|

Senolytic effects of quercetin in an in vitro model of pre-adipocytes and adipocytes induced senescence

Abstract: The dysfunction of adipose tissue with aging and the accumulation of senescent cells has been implicated in the pathophysiology of chronic diseases. Recently interventions capable of reducing the burden of senescent cells and in particular the identification of a new class of drugs termed senolytics have been object of extensive investigation. We used an in vitro model of induced senescence by treating both pre-adipocytes as well as mature adipocytes with hydrogen peroxide (H2O2) at a sub-lethal concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Quercetin is a flavonol known for its antioxidant, anti-inflammatory, antitumor, and senolytic properties [ 258 ]. Results obtained on different cell lines show that treatment with quercetin significantly lowers the levels of ROS and inflammatory cytokines, reduces the expression of SA-β gal, p16 and p53 and markedly increases that of the antioxidant enzymes SOD and CAT, regardless of the type of oxidative trigger used to induce senescence [ 258 , 259 , 260 , 261 , 262 ]. In addition to promoting the expression of Nrf2 [ 263 ], the beneficial action of quercetin appears to be mediated by the microRNA-155-5p, which is involved in the regulation of SIRT1 and NF-kB [ 262 , 264 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin is a flavonol known for its antioxidant, anti-inflammatory, antitumor, and senolytic properties [ 258 ]. Results obtained on different cell lines show that treatment with quercetin significantly lowers the levels of ROS and inflammatory cytokines, reduces the expression of SA-β gal, p16 and p53 and markedly increases that of the antioxidant enzymes SOD and CAT, regardless of the type of oxidative trigger used to induce senescence [ 258 , 259 , 260 , 261 , 262 ]. In addition to promoting the expression of Nrf2 [ 263 ], the beneficial action of quercetin appears to be mediated by the microRNA-155-5p, which is involved in the regulation of SIRT1 and NF-kB [ 262 , 264 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results obtained on different cell lines show that treatment with quercetin significantly lowers the levels of ROS and inflammatory cytokines, reduces the expression of SA-β gal, p16 and p53 and markedly increases that of the antioxidant enzymes SOD and CAT, regardless of the type of oxidative trigger used to induce senescence [ 258 , 259 , 260 , 261 , 262 ]. In addition to promoting the expression of Nrf2 [ 263 ], the beneficial action of quercetin appears to be mediated by the microRNA-155-5p, which is involved in the regulation of SIRT1 and NF-kB [ 262 , 264 ]. Moreover, as aging is associated with an inefficient protein-degradation (which is required to protect against OS), the effect of quercetin and its derivatives on the restoration of proteasomal functioning is of interest as rejuvenating strategy [ 265 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cellular senescence has been observed not only in RPTECs but also in various cells and tissues such as skin, liver, lung, adipose tissue, and vascular tissue. 9,[30][31][32][33] Therefore, the maximum limit of the number of passages should be defined for each cell type when primary cultured cells are used to evaluate the pharmacokinetics and toxicity of chemical compounds. In addition, we must also pay attention to other factors promoting cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…570 Dasatinib and quercetin have been found to eliminate both p16 high and p21 high senescent cells in the pancreas and adipose tissues in a T2DM animal model. 571,572 Unexpectedly, it has been reported that treatment with dasatinib and quercetin worsens liver disease progression in a diethylnitrosamine (DEN)/HFD mouse model, slightly increases histological damage and tumorigenesis, and has no effect on senescent cell removal. 573 Moreover, human senescent β cells also respond to senolysis, establishing the foundation for translation.…”
Section: Atherosclerosismentioning
confidence: 99%